2011
DOI: 10.1007/s12564-011-9148-y
|View full text |Cite
|
Sign up to set email alerts
|

Asian medical students: quality of life and motivation to learn

Abstract: Issues linked with the notions of quality of life (QOL) and motivation to learn among Asian medical students have not been well documented. This is true in both the international and the New Zealand contexts. Our paper addresses this lack of research by focusing on the QOL of international and domestic Asian students studying in New Zealand, where Asian students form a significant proportion of tertiary students. Although there is evidence to suggest that Asian students do well academically, it was felt that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Using a similar sample, Hsu et al [22] found that international students rated physical and environmental QoL lower than domestic students. In addition, Asian international students studying medicine in New Zealand were found to be more anxious about tests, whilst also scoring lower on environmental QoL than their domestic Asian peers [23]. These results are consistent with findings presented in studies conducted in other countries [24, 25].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Using a similar sample, Hsu et al [22] found that international students rated physical and environmental QoL lower than domestic students. In addition, Asian international students studying medicine in New Zealand were found to be more anxious about tests, whilst also scoring lower on environmental QoL than their domestic Asian peers [23]. These results are consistent with findings presented in studies conducted in other countries [24, 25].…”
Section: Introductionsupporting
confidence: 83%
“…It has been established that international students may be more at risk in reference to their QoL than their domestic peers [2123, 26]. However, the characteristics of these two groups and associations with QoL have not been investigated in medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include curriculum sequencing, clear learning needs, clear goals and well-defined learning objectives, assessment methods and tools, the standards being supported for documentation, development, assessment and teaching on these tools, appropriate levels of difficulty, reliable measures and reliable feedback mechanisms and advancement to the next tasks 3 32 33. However, there are several dimensions to be considered for better integration of these technologies for the surgical education programmes which can be summarised as below. Characteristics of medical students : Earlier studies show that there are significant differences between medical students and non-medical students considering their self-efficacy, intrinsic value and self-regulation characteristics 34. Students of secondary medical school achieve statistically significant higher results on the agreeableness scale compared with general education secondary schools35 and score higher on agreeableness36 where it may emerge from temperamental self-regulative systems37 as agreeableness describes warm and friendly personality.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of medical students : Earlier studies show that there are significant differences between medical students and non-medical students considering their self-efficacy, intrinsic value and self-regulation characteristics 34. Students of secondary medical school achieve statistically significant higher results on the agreeableness scale compared with general education secondary schools35 and score higher on agreeableness36 where it may emerge from temperamental self-regulative systems37 as agreeableness describes warm and friendly personality.…”
Section: Discussionmentioning
confidence: 99%